Entrepreneurship (New York : McGraw-Hill, 2010)
Features various articles from some of the most respected magazines, newspapers, and journals. This title is suitable for use in the classroom. It includes: a general introduction; an annotated table of contents; a topic guide; an annotated listing of selected world wide web sites; and, an overview for each section
BSBA
Keywords: Entrepreneurship -- Periodicals; New business enterprises